Types of Commentary Feedback - Kurnia Mukhlis; Suhartini Syukri (AL LUGHAWIYAAT, 2020)
This study aims to investigate types of lecturer commentary feedback on EFL students’ L2 writing through online class (Schoology) in writing class semester 4 of English Education major at IAIN Kendari. This study is conducted to classify types of commentary feedback which can help students to revise their own writing. Besides, this study is expected to ease another researcher or teacher to express their comments hsing these types of commentary feedback as a reference. This study utilized students’ draft as the instrument. To obtain the data, the researcher used qualitative research design. In analyzing the data, the researcher gathered students' draft which contained lecturer commentaries feedback that has been classified by coding the data to get the result. The result of this study reveals that there are five types commentary feedback that the lecturer applied to the students.